Stories from Langley : a glimpse inside the CIA - Mickolus, Edward F. (Potomac Books, An imprint of the University of Nebraska Press, 2014)
Applicants to the Central Intelligence Agency often asked Edward Mickolus what they might expect in a career there. Mickolus, a former CIA intelligence officer whose duties also included recruiting and public affairs, never had a simple answer. If applicants were considering a life in the National Clandestine Service, the answer was easy. Numerous memoirs show the lives of operations officers collecting secret intelligence overseas, conducting counterintelligence investigations, and running covert action programs. But the CIA isn't only about case officers in far-flung areas of the world, recr.